Long-Term Follow-up Posthematopoietic Stem Cell Transplantation in a Japanese Patient with Type-VII Mucopolysaccharidosis - Orii, Kenji (Diagnostics (Basel), 2020)
The effectiveness of hematopoietic stem cell transplantation (HSCT) for type-VII mucopolysaccharidosis (MPS VII, Sly syndrome) remains controversial, although recent studies have shown that it has a clinical impact. In 1998, Yamada et al. reported the first patient with MPS VII, who underwent HSCT at 12 years of age. Here, we report the results of a 22-year follow-up of that patient post-HSCT, who harbored the p.Ala619Val mutation associated with an attenuated phenotype. The purpose of this study was to evaluate changes in physical symptoms, the activity of daily living (ADL), and the intellectual status in the 34-year-old female MPS VII patient post-HSCT, and to prove the long-term effects of HSCT in MPS VII. Twenty-two years after HSCT, the β-glucuronidase activity in leukocytes remained at normal levels, and urinary glycosaminoglycan excretion was reduced and kept within normal levels. At present, she is capable of sustaining simple conversation, and her intellectual level is equivalent to that of a 6-year-old. She can walk alone and climb upstairs by holding onto a handrail, although she feels mild pain in the hip joint. The cervical vertebrae are fused with the occipital bone, causing dizziness and light-headedness when the neck is bent back. Overall, her clinical condition has been stabilized and kept well for long-term post-HSCT, indicating that HSCT is a therapeutic option for MPS VII.